Parasitoids follow herbivorous insects to a novel host plant, generalist predators less so. Issue 3 (2nd March 2017) - Grosman, Amir H.; Holtz, Anderson Mathias; Pallini, Angelo; Sabelis, Maurice W.; Janssen, Arne
Abstract: The 'enemy‐free space' hypothesis predicts that herbivorous insects can escape their natural enemies by switching to a novel host plant, with consequences for the evolution of host plant specialisation. However, if natural enemies follow herbivores to their novel host plants, enemy‐free space may only be temporary. We tested this by studying the colonisation of the introduced tree Eucalyptus grandis (Hill) Maiden (Myrtaceae) by insects in Brazil, where various species of herbivores have added eucalyptus to their host plant range, which consists of native myrtaceous species such as guava. Some herbivores, for example, Thyrinteina leucoceraea Ringe (Lepidoptera: Geometridae), cause outbreaks in eucalyptus plantations but not on guava, possibly because eucalyptus offers enemy‐free space. We sampled herbivores (mainly Lepidoptera species) and natural enemies on eucalyptus and guava and assessed parasitism of Lepidoptera larvae on both host plant species during ca. 2 years. Overall, predators were encountered more frequently on guava than on eucalyptus. In contrast, parasitoids were encountered equally and parasitism rates of Lepidoptera larvae were similar on both host plants. This indicates that herbivores may escape some enemies by moving to a novel host plant. However, this escape may be temporary and may vary with time. We argue that studying temporal and spatial patterns of enemy‐free space and the response of natural enemies to host use changes of their herbivorous prey is essential for understanding the role of natural enemies in the evolution of host plant use by herbivorous arthropods.